Urban architectural project "land terminal for regional passenger transport to the high Andean areas of the city of Tacna 2015" - Apaza Sosa, Jasmani Ernesto (2016)
The city is mobility that is born three thousand years ago as a space for interaction between citizens and businesses and, therefore, prosperity. So is being since then and especially in the last two centuries, which will, of technological advances in transport, uncharacteristically progressing thresholds city, overflowing again and again the old and outdated administrative divisions at the beginning of the century XIX in search of the paradigm of comprehensive process of advanced societies: quality of life and productivity of large scale employment and training. Objective. Determine the influence of regional transport infrastructure in the care of passengers to the highlands of the city of Tacna - 2015. Method: The methodology used was explanatory research. With this type of research will seek to discover, establish and explain the functional relationships between the variables studied, explain how, when, where and why they occur phenomena related to the subject of study, which will be part of the conditions for well achieve a proposal according to the needs of the population of Tacna. Results: As a result of the research project architectural bus terminal for regional transport of passengers to the highlands it was developed, considering their respective merits. Conclusions: Contribute to the knowledge of the aspects that establish requirements for the design functional spaces with proper operation of regional bus terminal having a service coverage for the high Andes department of Tacna and surrounding areas.